2022
DOI: 10.1088/1555-6611/ac52b0
|View full text |Cite
|
Sign up to set email alerts
|

Direct and 2f-wavelength modulation spectroscopy of NO and OCS using an astigmatic multipass cell coupled with a mid-IR 5.2 µm cw-QCL

Abstract: We developed a mid-IR 2f-wavelength modulation spectroscopy (WMS) detection system combining a continuous wave external-cavity quantum cascade laser (QCL) at 5.2 μm and an astigmatic multipass cell. The high-sensitivity performance of the 2f-WMS system was validated by simultaneously probing the strongest interference-free absorption lines of Λ-doublet components of R (6.5) rotational line in 2Π1/2 magnetic electronic sub-state of nitric oxide (NO) centred at 1900.0706 cm−1 and the R (18) rotational line of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We have measured the absorption of calibrated NO 2 samples which are standardized by our previously reported method [39] and subsequently, the effective optical path-length of the current setup has been measured by using the Beer-Lambert law:…”
Section: Determination Of the Optical Path-length Mirror Reflectivity...mentioning
confidence: 99%
“…We have measured the absorption of calibrated NO 2 samples which are standardized by our previously reported method [39] and subsequently, the effective optical path-length of the current setup has been measured by using the Beer-Lambert law:…”
Section: Determination Of the Optical Path-length Mirror Reflectivity...mentioning
confidence: 99%
“…TDLAS has good sensitivity and quantitative performance and is one of the most promising approaches at present [ 20 , 21 ]. It has been successfully applied to trace gas detection in ambient environments [ 22 , 23 , 24 ]. However, only a few studies have been reported on trace gas detection in harsh environments.…”
Section: Introductionmentioning
confidence: 99%